PetXi: online pet care and transportation service / Arman Fikri Mohd Fuad ... [et al.] - Mohd Fuad, Arman Fikri; Muhammad Ridzuan, Mia Khalysah; Morshidi, Nur Munira; Wahib, Sofea Qistina; Murad, Khairudin (2022)
Given pet owners’ busy schedules today, they sometimes struggle to provide for their pets' requirements independently. Finding the time to take their animals to the vet can be difficult, especially if someone is not available to help. These pet owners would benefit greatly from having a smartphone app specialising in pet services, so they do not have to worry about their pets not getting what they need. PetXi's goals are to make it easier for pet owners with busy schedules to take care of their pets' requirements and transport them safely to and from the neighbouring doctor and grooming appointments. This application employs comparative and observational research examining Malaysia's pet-care market.